Tributación en servicios digitales - Medrano Cornejo, Humberto (2021)
ADVOCATUS had the opportunity to interview Humberto Medrano Cornejo, a Peruvian lawyer expert in tax law. He has been president of the Peruvian Institute of Tax Law — IPDT, as well as a founding member of the Fiscal International Association and Director of the Latin American Institute of Tax Law. Throughout the lines below, he offers us his opinions on digital expansion and the challenges for its taxation.